Effects of ocean alkalinity enhancement on plankton in the Equatorial Pacific - Jiaying A. Guo; Robert F. Strzepek; Zhongwei Yuan; Kerrie M. Swadling; Ashley T. Townsend; Eric P. Achterberg; Thomas J. Browning; Lennart T. Bach (Communications Earth & Environment)
Abstract Ocean alkalinity enhancement is a potential strategy for gigatonne-scale atmospheric carbon dioxide removal. It uses alkaline substances to convert seawater carbon dioxide into (bi)carbonate, enabling uptake of additional carbon dioxide from the atmosphere. A critical knowledge gap is how ocean alkalinity enhancement could influence marine plankton communities. Here we conducted 19 ship-based experiments in the Equatorial Pacific, examining three prevalent alkaline substances (sodium hydroxide, olivine, and steel slag) and their effects on natural phytoplankton populations under realistic and moderate alkalinity enhancements (16–29 μmol kg−1). Results demonstrate that sodium hydroxide had a negligible effect on phytoplankton while providing predictable alkalinity. Conversely, olivine disrupted plankton, especially cyanobacteria, heterotrophic bacteria, and picoeukaryotes while only providing 0.06 mmol alkalinity g−1 olivine. Steel slag moderately changed phytoplankton communities and fertilized growth while delivering 8 mmol alkalinity g−1 slag. Our study helps to determine which alkaline substance could be suitable for application in the Equatorial Pacific.